2000
DOI: 10.1074/jbc.m002785200
|View full text |Cite
|
Sign up to set email alerts
|

Channel Formation by the Glycosylphosphatidylinositol-anchored Protein Binding Toxin Aerolysin Is Not Promoted by Lipid Rafts

Abstract: Glycosylphosphatidylinositol-anchored proteins may be concentrated in membrane microdomains (lipid rafts) that are also enriched in cholesterol and sphingolipids. The glycosyl anchor of these proteins is a specific, high affinity receptor for the channel-forming protein aerolysin. We wished to determine if the presence of rafts promotes the activity of aerolysin. Treatment of T lymphocytes with methyl-␤-cyclodextrin, which destroys lipid rafts by sequestering cholesterol, had no measurable effect on the sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…We believe that the cyclic AMP is specifically released outside of the cell. The reports from Buckley's group support our hypothesis about the specific release of cyclic AMP (10,11,12,13). These authors showed that channels that are relatively nonselective are formed in the cell membrane after the incubation with aerolysin.…”
Section: Fig 2 Effects Of Ada Xacsupporting
confidence: 75%
“…We believe that the cyclic AMP is specifically released outside of the cell. The reports from Buckley's group support our hypothesis about the specific release of cyclic AMP (10,11,12,13). These authors showed that channels that are relatively nonselective are formed in the cell membrane after the incubation with aerolysin.…”
Section: Fig 2 Effects Of Ada Xacsupporting
confidence: 75%
“…It has been further reinforced by the finding that aerolysin heptamers formed in DRMs move to a non-DRM fraction upon treatment with saponin, a cholesterol-binding agent (9). The cytotoxicity and heptamerization of aerolysin in T lymphocytes, however, are insensitive to MbCD treatment, thus arguing against the dependence of aerolysin heptamerization on DRMs (33). A plausible explanation for these apparently contradictory observations is that cholesterol depletion affects heptamerization in most cell types but not in T lymphocytes expressing unusually high levels of aerolysin receptors (10).…”
Section: Discussionmentioning
confidence: 89%
“…Approximately 90% of the total hRBC cholesterol was removed primarily because erythrocyte cholesterol is almost entirely associated with the plasma membrane of erythrocytes (20).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of cholesterol depletion on the sensitivity of hRBCs to lysis by PFO, SLO, or ILY was initially examined to confirm that the cytolytic mechanism of all three toxins was indeed sensitive to the loss of membrane cholesterol. The hemolytic dose for 50% lysis (HD 50 , see Materials and Methods) was determined for each toxin by using native hRBCs and hRBCs depleted of Ϸ90% of their membrane cholesterol (Table 1) with the cholesterol-sequestering agent M␤CD (20,26).…”
Section: Depletion Of Membrane Cholesterol Abolishes Cdc-dependent Ermentioning
confidence: 99%